Gender Fluidity in Contemporary Menswear: A Deleuzian Analysis and Gen Z Narratives - Githapradana, Dewa Made Weda (Humaniora: Journal of Indonesia Culture and Society, 2025)
The market identity for menswear is undergoing a significant transformation toward a more diverse and inclusive range of options, primarily due to the rise of gender-fluid fashion. Research indicates that menswear evolves to offer a greater variety of gender-fluid and diverse clothing choices for the average male consumer, reflecting a shift in fashion consumption and expressions of masculinity. Notable trends reshaping the fashion landscape include the embrace of gender-flexible fashion and the rejection of toxic masculinity among Generation Z (Gen Z) men. The research aims to explore the trend of gender fluidity in contemporary menswear through a Deleuzian lens. It focuses on applying the theory of the senses and the concept of “becoming” based on the philosophical work of Gilles Deleuze and Félix Guattari. The analysis centers around a fashion design project titled Soul Equilibrium, which serves as the case study. Deleuzian theory is employed to examine the relationship between trend fluidity and changes in gender performativity as expressed through fashion. Qualitative data are gathered through observations, interviews, and literature reviews, with respondents selected through purposive sampling. These respondents include experts and individuals actively engaged in fashion. Key findings reveal that the intersection of gender-fluid fashion and performativity fosters a dynamic relationship among fashion, identity, and societal norms. Gender-fluid fashion emerges as a significant indicator of changing gender performativity in society. The concept of gender performativity highlights how individuals actively construct their gender identity through behavior and self-expression. The results of the research advocate for greater social acceptance and inclusivity within society.